You are so undead to me - Jay, Stacey (Razorbill, 2009)
Sequel: Undead much. -- Megan Berry, a Carol, Arkansas, high school student who can communicate with the Undead, must team up with her childhood friend Ethan to save homecoming from an army of flesh-hungry zombies.